2005
DOI: 10.1590/s0037-86822005000400005
|View full text |Cite
|
Sign up to set email alerts
|

O perfil dos portadores de doença de Chagas, com ênfase na forma digestiva, em hospital terciário de Ribeirão Preto, SP

Abstract: Para caracterizar o perfil clínico e demográfico dos portadores da forma digestiva da doença de Chagas atualmente atendidos no Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto, foram revistos 377 prontuários de pacientes com resultado positivo para reação sorológica para a doença de Chagas atendidos entre janeiro de 2002 a março de 2003. A idade mediana dos pacientes era de 67 anos e 210 (56%) eram mulheres. Megaesôfago e/ou megacólon chagásicos estavam presentes em 135 pacientes, dos quais, 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
2
12
0
6
Order By: Relevance
“…Regarding distribution by gender, similar to the fi ndings of Rezende 13 , Rezende and Luquetti 18 and Vaz et al 21 , this study found that males were generally more prevalent (54% of cases) relative to females (46% of cases). However, studies performed by Kamiji and Oliveira 20 and Almeida et al 24 demonstrated a greater prevalence of female patients, and Peñaranda-Carrillo et al 25 and Oliveira et al 19 did not observe any gender differences in their studies. The predominance of CM in a given gender has resulted in many studies with controversial results.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Regarding distribution by gender, similar to the fi ndings of Rezende 13 , Rezende and Luquetti 18 and Vaz et al 21 , this study found that males were generally more prevalent (54% of cases) relative to females (46% of cases). However, studies performed by Kamiji and Oliveira 20 and Almeida et al 24 demonstrated a greater prevalence of female patients, and Peñaranda-Carrillo et al 25 and Oliveira et al 19 did not observe any gender differences in their studies. The predominance of CM in a given gender has resulted in many studies with controversial results.…”
Section: Discussionmentioning
confidence: 81%
“…For example, the median in the study performed by Kamiji and Oliveira 20 was 67 years, and the study conducted by Meneghelli et al 23 revealed that a median of 55 years. Thus, the prevalence of older patients (> 40 years old) with CM deserves special attention, not only with regard to esophagopathy but also other comorbidities that are prevalent in the population in this age group, such as cardiovascular and metabolic diseases 19 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Chagas disease is a major public health problem that is largely restricted to South America, 1,2 where it affects 15 million individuals. The combined annual incidence is 42,000 cases in 21 countries 3 .…”
Section: B Introductionmentioning
confidence: 99%